Integrating Artificial Intelligence into the Design Process: Implications for Creativity and Innovation - Fitro Nur Hakim; Wiwid Wahyudi; Nur Rokhman (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Artificial Intelligence (AI) has significantly transformed the design industry by introducing innovative tools that enhance efficiency, creativity, and personalization in the design process. This article explores the impact of AI technologies on the practice of modern designers, from the early stages of idea generation to the final execution of projects. By analyzing case studies, conducting surveys, and reviewing recent literature, the study reveals that AI functions not only as a tool but also as a collaborator that expands the boundaries of human creativity. It allows designers to explore new possibilities and push the limits of traditional design processes. However, the integration of AI into design practices also raises important ethical and professional challenges, such as concerns about job displacement, data privacy, and the potential loss of human touch in the creative process. Despite these concerns, the findings highlight that embracing AI is crucial for designers to remain competitive and sustain their careers in the rapidly evolving digital era. Adapting to AI technologies, understanding their capabilities, and effectively incorporating them into creative workflows will enable designers to stay relevant and thrive in a landscape where technology continues to reshape the industry. This study provides insights into the evolving relationship between human designers and AI, offering recommendations for future research and practice in the field of design.